Direct Comparison of the Performance of Commonly Employed In Vivo F-actin Markers (Lifeact-YFP, YFP-mTn and YFP-FABD2) in Tobacco Pollen Tubes - Montes-Rodriguez, Adriana; Kost, Benedikt (Frontiers in Plant Science, 2017)
In vivo markers for F-actin organization and dynamics are extensively used to investigate cellular functions of the actin cytoskeleton, which are essential for plant development and pathogen defense. The most widely employed markers are GFP variants fused to F-actin binding domains of mouse talin (GFP-mTn), Arabidopsis fimbrin1 (GFP-FABD2) or yeast Abp140 (Lifeact-GFP). Although numerous reports describing applications of one, or occasionally more, of these markers, are available in the literature, a direct quantitative comparison of the performance of all three markers at different expression levels has been missing. Here, we analyze F-actin organization and growth rate displayed by tobacco pollen tubes expressing YFP-mTn, YFP-FABD2 or Lifeact-YFP at different levels. Results obtained establish that: 1) all markers strongly affect F-actin organization and cell expansion at high expression levels, 2) YFP-mTn and Lifeact-YFP non-invasively label the same F-actin structures (longitudinally oriented filaments in the shank, a subapical fringe) at low expression levels, 3) Lifeact-YFP displays a somewhat lower potential to affect F-actin organization and cell expansion than YFP-mTn, and 4) YFP-FABD2 generally fails to label F-actin structures at the pollen tube tip and affects F-actin organization as well as cell expansion already at lowest expression levels. As pointed out in the discussion, these observations 1) are also meaningful for F-actin labeling in other cell types, which generally respond less sensitively to F-actin perturbation than pollen tubes, 2) help selecting suitable markers for future F-actin labeling experiments, and 3) support the assessment of a substantial amount of published data resulting from such experiments.